Evaluation of the sialic acid content of LDL as a marker of coronary calcification and extracoronary atherosclerosis in asymptomatic hypercholesterolemic subjects. PCVMETRA Group - Chappey, B; Myara, I; Giral, P; Kerharo, G; Plainfosse, M C; Levenson, J; Simon, A; Moatti, N (Arteriosclerosis, thrombosis, and vascular biology, 1995)
Recent studies have shown that the sialic acid content of LDL isolated from patients with angiographically demonstrated advanced coronary atherosclerosis is lower than that of LDL isolated from healthy subjects. These observations raise the question as to whether LDL sialic acid content could be used as an early marker of atherosclerosis. We screened for carotid, aortic, and femoral plaques by ultrasonography and for coronary calcifications by ultrafast computed tomography in 160 hypercholesterolemic subjects free of cardiovascular disease to investigate the relation between LDL sialic acid content and the prevalence of these early atherosclerotic lesions. LDL sialic acid values varied from 19.6 to 46.6 nmol/mg LDL protein (33.9 +/- 4.4, mean +/- SD) in the whole population, but the distribution was very similar: (1) in subjects with no plaque (34.1 +/- 4.9) relative to those with one or several plaques at one (34.2 +/- 4.4), two (33.0 +/- 3.6), or three (34.8 +/- 3.4) different arterial sites; (2) in subjects with (33.9 +/- 3.7) and without (34.1 +/- 4.8) coronary calcification; and (3) in subjects with both extracoronary and coronary lesions (33.8 +/- 3.9) relative to those with no arterial lesions (34.2 +/- 4.5). LDL sialic acid content was not related to sex, age, body mass index, smoking, blood pressure, or serum total cholesterol and lipoprotein(a) levels but correlated negatively with serum triglyceride levels (P < .001). These results suggest that LDL sialic acid content is not a discriminant marker of early atherosclerosis in asymptomatic hypercholesterolemic subjects.